2019
DOI: 10.1029/2018wr024592
|View full text |Cite
|
Sign up to set email alerts
|

Predicting CO2 Plume Migration in Heterogeneous Formations Using Conditional Deep Convolutional Generative Adversarial Network

Abstract: Numerical simulation of flow and transport in heterogeneous formations has long been studied, especially for uncertainty quantification and risk assessment. The high computational cost associated with running large‐scale numerical simulations in a Monte Carlo sense has motivated the development of surrogate models, which aim to capture the important input‐output relations of physics‐based models but require only a fraction of the cost of full model runs. In this work, we formulate a conditional deep convolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(50 citation statements)
references
References 56 publications
0
50
0
Order By: Relevance
“…Mao et al (2016) showed that the use of skip connections helps the training process to converge much faster and attain a higher-quality local optimum. So far, U-Net and its variants have been used in a large number of DL applications in geosciences (Sun, 2018;Arge et al, 2019;Karimpouli and Tahmasebi, 2019;Mo et al, 2019;Zhong et al, 2019;Zhu et al, 2019).…”
Section: Attention-based Deep Convolutional Neural Netmentioning
confidence: 99%
“…Mao et al (2016) showed that the use of skip connections helps the training process to converge much faster and attain a higher-quality local optimum. So far, U-Net and its variants have been used in a large number of DL applications in geosciences (Sun, 2018;Arge et al, 2019;Karimpouli and Tahmasebi, 2019;Mo et al, 2019;Zhong et al, 2019;Zhu et al, 2019).…”
Section: Attention-based Deep Convolutional Neural Netmentioning
confidence: 99%
“…For this study, CycleGAN is implemented by using deep convolutional neural networks, as shown in Zhong, Sun, and Jeong () (Figure ). Similar to the original CycleGAN design presented in Zhu et al (), the two generative models share the same end‐to‐end deep learning neural network architecture, which includes a series of convolutional layers to extract fine‐scale features from the input data, followed by a series of deconvolutional layers to learn coarse‐scale features and to generate a target image that has the same sizes as the input data (i.e., 128×128).…”
Section: Methodsmentioning
confidence: 99%
“…The two factors together make the commonly used surrogate methods, such as Gaussian processes (Rasmussen & Williams, ) and polynomial chaos expansion (Xiu & Karniadakis, ), difficult to work. Deep neural networks have already exhibited a promising and impressive performance for surrogate modeling of forward models with high‐dimensional input and output fields (Kani & Elsheikh, ; Mo, Zabaras, et al, ; Mo, Zhu, et al ; Sun, ; Tripathy & Bilionis, ; Zhong et al, ; Zhu & Zabaras, ; Zhu et al, ). For example, in Tripathy and Bilionis () a deep neural network was proposed to build a surrogate model for a single‐phase flow forward model.…”
Section: Introductionmentioning
confidence: 99%